Effects of Single Loading Dose of Intravenous Caffeine on Cerebral Oxygenation in Preterm Infants - Ilhan, Ozkan; Bor, Meltem (American Journal of Perinatology, 2020)
Objective The aim of this study was to evaluate the effects of caffeine on cerebral oxygenation in preterm infants.Study Design This was a prospective study of infants with a gestational age (GA) of < 34 weeks who were treated intravenously with a loading dose of 20 mg/kg caffeine citrate within the first 48 hours of life. Regional cerebral oxygen saturation (rSO2C) and cerebral fractional tissue oxygen extraction (cFTOE) were measured using near-infrared spectroscopy before administering caffeine (baseline), immediately after administering caffeine, and 1, 2, 3, 4, 6, and 12 hours after dose completion; postdose values were compared with the baseline values.Results A total of 48 infants with a mean GA of 29.0 ± 1.9 weeks, birth weight of 1,286 ± 301 g, and postnatal age of 32.4 ± 11.3 hours were included in the study. rSO2C significantly decreased from 81.3 to 76.7% soon after administering caffeine, to 77.1% at 1 hour, and to 77.8% at 2 hours with recovery at 3 hours postdose. rSO2C was 80.2% at 12 hours postdose. cFTOE increased correspondingly. Although rSO2C values were lower and cFTOE values were higher compared with the baseline values at 3, 4, 6, and 12 hours after caffeine administration, this was not statistically significant.Conclusion A loading dose of caffeine temporarily reduces cerebral oxygenation and increases cerebral tissue oxygen extraction in preterm infants. Most probably these changes reflect a physiological phenomenon without any clinical importance to the cerebral hemodynamics, as the reduction in cerebral oxygenation and increase in cerebral tissue oxygen extraction remain well within acceptable range.
Keywords: caffeine; cerebral oxygenation; near-infrared spectroscopy; preterm infant; oxygen saturation